The impact of ESG on firm value: The moderating role of cash holdings - Omnia Ahmed; Bashar Abu Khalaf (Heliyon)
This paper examines whether Environmental, Social, and Governance (ESG) performance has an impact on companies' market value and cash holdings. Drawing from 27 European Union countries, a comprehensive sample of 1144 companies was collected from LSEG Data & Analytics over an 11-year period (2013–2023). This research applied panel regression (fixed and random effect techniques) to investigate the relationships; based on the significant result of a Hausman test, the fixed effect regression has been analyzed. The results show that the more efficient and effective the ESG performance, the higher the company value. In addition, cash holdings affect the market value positively, which indicates that as companies hold high cash reserves, their market value increases. The main recommendation provided to different board members in the EU region is to follow the ESG principles and guidelines and to hold more cash since this should substantially raise the company's value. Our results are robust since the Tobit regression provided results similar to those of the fixed effect technique.